THE USE OF KAHOOT! MEDIA IN ELEMENTARY SCHOOLS: SYSTEMATIC LITERATURE REVIEW - Arifa, Dian Nur; Sularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This study examines the use of Kahoot! as an interactive learning medium in Elementary Schools. Through a systematic literature review, it was found that Kahoot! is effective in increasing student motivation, participation, and understanding. The results of this study support the use of game-based technology for fun learning that is in accordance with student characteristics. The purpose of this study was to analyze the effectiveness of using Kahoot! in increasing student motivation and understanding in learning in Elementary Schools. This study uses the Systematic Literature Review method to identify, collect, and analyze scientific articles related to the use of Kahoot! in learning in Elementary Schools. The review process was carried out through the PRISMA stages which include identification, screening, eligibility, and exclusion based on certain criteria. The articles analyzed were selected based on the suitability of the topic, research method, year of publication, and relevance to students' attitudes towards the use of Kahoot! learning media. The use of Kahoot! has proven to be beneficial in increasing student motivation, participation, and understanding, although there are still challenges such as limited time, internet access, and infrastructure readiness. In general, students show a positive attitude towards learning using Kahoot!, but its effectiveness still requires the active role of teachers in planning and implementation. This study contributes by showing that Kahoot! effectively supports interactive learning and improves the affective, cognitive, and psychomotor aspects of elementary school students.